Política Linguística de acolhimento a crianças imigrantes no ensino fundamental brasileiro: Um estudo de caso - Amélia de Oliveira Neves (2018)
The current world migratory crisis (ACNUR, 2017) has led to an increased number of enrollments by immigrant students in Brazilian regular schools (UNIBANCO, 2018), many of whom have a low level of proficiency in Portuguese. Despite the access of those students to Basic Education is worldwide assured by law, it is important to analyze whether the language policies implemented by schools favor the learning of Portuguese, considering that this is, in general, the single language of instruction in the institutions where those children are enrolled. Immigrant students whose mother tongue is different from Portuguese have specific needs while compared to the other students and factors such as the distance between the language(s) they speak and Portuguese should be taken in consideration. Some media reports in 2016 and 2017 point out a possible lack of readiness of Brazilian schools in dealing with that public. It is upon this juncture that, aligned with the perspective of the Indisciplinary Applied Linguistics (MOITA LOPES, 2006), we propose to carry out a case study on Nina (fictitious name), a Syrian child that, in early 2016, started the third grade of the Elementary School in a public school in Belo Horizonte-MG, Brazil. The objective of our study is to analyze the language policy for the reception of Nina, explicitly or implicitly implemented by her school. To do so, we sought to identify the actions taken to promote Nina´s integration into the school environment; to analyze challenges and impasses to implement hat policy, to propose actions that may contribute to an effective welcoming policy for Nina and for other foreign and Brazilian students who do not have Portuguese as their first language. We could observe that the school we focused in this study sought the support of a professional in the area of Portuguese as a Welcoming Language (PWL), and that it also counted on an assistant as support for inclusive education, who accompanied one of the Syrian students classmate. However, we found some impasses in the welcoming policy for Nina: we wondered how to make her cultural and linguistic differences visible without exposing her as exotic to the group and how to welcome her without reinforcing the helplessness image usually attributed to the refugees (LOPEZ, 2016). Other challenges were the issues involving the communication between the school and Nina´s family and the teaching of the host language without loss of mother tongue. Amongst the possible actions that could have contributed to a proper welcoming policy for Nina, we have identified the following: promoting more opportunities for the accomplishment of intercultural dialogues; establishing better communication between the teacher of Portuguese as a Welcoming Language and the school; avoiding actions that could either obscure Ninas linguistic and cultural differences or reinforce the vulnerability often attributed to people in refugee situations; improving the dialogue between school and family; increasing PWL class hours, offering Portuguese classes to Nina´s relatives, promoting the students literacy in Arabic and adapting the visual communication within the school. It is expected that such work contributes to the treatment, in elementary schools, of children who do not have Portuguese as their first language, particularly, the immigrant ones, as well as for structuring public policies aimed at the welcoming of such students.